Practical temperature measurement - Childs, Peter R. N. (Butterworth-Heinemann, 2001)
'Practical Temperature Measurement' introduces the concepts of temperature and its measurement to engineers, physicists and chemists of all disciplines. The author describes the wide range of techniques and specific devices available for temperature measurement and provides guidance for the selection of a particular method for a given application. It is of value to engineering and physics postgraduates studying modules on instrumentation and process control and, in addition, for practical project work requiring an understanding of temperature measurement methods. For postgraduates and industria.